2006
DOI: 10.3892/ijo.28.6.1463
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase-type plasminogen activator induces proliferation in breast cancer cells

Abstract: Abstract. Urokinase-type plasminogen activator (uPA) is implicated in various pathophysiological processes, including extracellular matrix turnover, cell migration and invasion. Our study aimed to determine the role of uPA in both proliferation and mitogen-activated protein kinase (MAPK) pathway. Hence, we analyzed the effects induced by exogeneous addition of domain-specific uPA antibodies and uPAinteracting molecules on proliferation of uPA-suppressed MDA-MB-231 breast cancer cells. uPA expression was reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
2
13
0
1
Order By: Relevance
“…Several earlier studies have reported the increased expression of uPAR in various types of cancers (8,14,42) and also its localization and active role at the tumor invasion front (15,43). Furthermore, earlier reports suggested a strong role for uPAR in cell adhesion since uPAR consists of a site for binding to vitronectin (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several earlier studies have reported the increased expression of uPAR in various types of cancers (8,14,42) and also its localization and active role at the tumor invasion front (15,43). Furthermore, earlier reports suggested a strong role for uPAR in cell adhesion since uPAR consists of a site for binding to vitronectin (44).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the uPA-uPAR system brings about several intracellular and intercellular processes including cleavage and activation of plasminogen to plasmin, remodeling of extracellular matrix (ECM), activation of growth factors, and initiation of intracellular signaling in response to various stimuli (7). As such, the uPAuPAR system plays a crucial role in cell adhesion, migration, invasion and cell proliferation, particularly in an altered environment such as cancer (8). Overexpression of uPAR has been reported in various cancers (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that uPAR gene amplifications render the tumor more sensitive to the prosurvival and antiapoptotic signals of uPA. Recent reports showed that uPAR/uPA-induced proliferation involves activation of ERKs and p38 MAP kinases 11,12 either directly or via release of different growth factors and through dynamic control of cell-matrix interactions. In agreement with previous reports, 24 we found strong uPAR expression in tumor-associated macrophages and fibroblasts of the tumor stroma.…”
Section: Discussionmentioning
confidence: 99%
“…Integrins situated adjacent to uPAR carry the signals into the cell, thus stimulating proliferation that is mediated via the mitogen-activated protein kinase (MAPK) pathway. 11 The ability of uPA to activate the MAPK pathway by binding to uPAR was reported previously. 6,[12][13][14] There appears to exist a positive feedback loop between uPAR/uPA expression and MAPK: the uPAR/uPA system plays a critical role in maintaining a high level of activated MAPK and at the same time, activated MAP kinases are necessary to maintain uPA and uPAR expression.…”
mentioning
confidence: 99%
“…gyetko и кол-леги показали, что у мышей, нокаутных по урокиназе, пролиферация т-клеток оказалась сниженной [99]. на раковых клетках была по-казана способность ростового домена уроки-назы запускать клеточную пролиферацию на остеобластоподобных клетках [100], клетках меланомы [101], клетках остеосаркомы челове-ка saos-2, раковых клетках молочной желе-зы [102,103]. причем для этого эффекта не-обходимым являлось фукозилирование thr18 в ростовом домене урокиназы [104].…”
Section: пролиферация и апоптозunclassified